PERTIMBANGAN HAKIM MEMERIKSA DAN MEMUTUS PERKARA PENGANIAYAAN DALAM PUTUSAN NOMOR: 66/PID.B/2023/PN SKT - Soesanto, Aldi Danuarta; Santoso, Bambang (Verstek, 2026)
This article analyzes the judge's considerations in adjudicating the criminal case of assault in Verdict Number 66/Pid.B/2023/PN Skt, which evaluates the evidentiary strength of witness testimony against the defendant Sutiyo Tejo Prabowo, as charged by the public prosecutor. This type of research is normative legal research that is prescriptive and applied in nature, using a case-based approach withprimary and secondary legal materials. The technique for collecting legal materials was conducted through literature studies, followed by an analysis technique using the deductive method. Based on the research findings and discussion, it was shown that the judge's considerations in rendering a verdict in the defendant's criminal assault case in Verdict Number 66/Pid.B/2023/PN Skt were in accordance with Article183 of the Indonesian Criminal Procedure Code (KUHAP).